Implementasi Pajak terhadap Cryptocurrency di Indonesia - Dodi Prandika YB; Andi Sharon Syahputra MM; Felix Andika K. Seda Ngga’u (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Cryptocurrency is a blockchain-based technology that is used for all activities so that it has the potential to increase state revenue, especially in terms of taxation. This study aims to determine the implementation of tax policies on Cryptocurrency transactions in Indonesia. This research uses descriptive qualitative methods using secondary and primary data. Secondary data is obtained through journals, books, and tax laws. Based on this research Cryptocurrency can be subject to income tax and value added tax. The results of this study indicate that the implementation of tax policies on crypto asset transactions in Indonesia has referred to the provisions as stated in PMK Number 68 / PMK.03 / 2022. However, there are still some weaknesses in the implementation of this tax policy on crypto asset transactions. In addition, in terms of supervision, it still only adheres to supervision of formal tax obligations. Therefore, supervision of the implementation of tax policies on crypto asset transactions still needs to be improved.